2000
DOI: 10.1161/01.cir.101.21.2461
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of the Cholesteryl Ester Transfer Protein ( CETP ) Gene to LDL Particle Size

Abstract: Background-A preponderance of small, dense LDL particles, elevated levels of plasma triglycerides (TG), and low levels of HDL characterize the atherogenic lipoprotein phenotype, which is associated with increased coronary artery disease (CAD) risk. Genetic and environmental factors influence LDL size, cholesteryl ester transfer protein (CETP) being one of the candidate genes. CETP mediates the transfer of cholesteryl ester from HDL to apolipoprotein (apo) B-containing lipoproteins in exchange for TG, promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Increased levels of sdLDL are highly atherogenic and increase the risk of CVD. A linkage of CETP locus to LDL particle size has been previously reported [34]. The I405V polymorphism has been reported to be associated with LDL size [7].…”
Section: Discussionmentioning
confidence: 91%
“…Increased levels of sdLDL are highly atherogenic and increase the risk of CVD. A linkage of CETP locus to LDL particle size has been previously reported [34]. The I405V polymorphism has been reported to be associated with LDL size [7].…”
Section: Discussionmentioning
confidence: 91%
“…It has been demonstrated that cholesteryl ester transfer protein (CETP) is also an important determinant of LDL particle size 25,26) . In addition, lipoprotein lipase (LPL) activity and hepatic lipase activity have been shown to contribute to the formation of sd-LDL particles and could well represent significant determinants of LDL-peak particle diameter (LDL-PPD) in FH 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Cholesteryl ester transfer protein (CETP) plays a major role in the remodeling of lipoprotein particles by mediating the transfer of cholesteryl ester from HDL to apolipoprotein B (apoB)-containing lipoproteins in exchange for triglycerides, and several lines of evidence support the notion that CETP is linked to LDL size heterogeneity (4). Small, dense LDL particles have been associated with CAD in a number of studies (5)(6)(7).…”
mentioning
confidence: 99%